Factors associated with limitation of care after fatal injury. Issue 6 (15th June 2022) - de Angelis, Paolo; Meredyth, Nicole; Leahy, Nicole E.; An, Anjile; Narayan, Mayur; Barie, Philip S.; Winchell, Robert J.
Abstract : BACKGROUND: There is variability in end-of-life care of trauma patients. Many survive resuscitation but die after limitation of care (LoC). This study investigated LoC at a level I center. METHODS: Adult trauma deaths between January 2016 and June 2020 were reviewed. Patients were stratified into "full code" versus any LoC (i.e., do not resuscitate, no escalation, or withdrawal of care) and by timing to LoC. Emergency department and "brain" deaths were excluded. Unadjusted logistic regression and Cox proportional hazards were used for analyses. Results include n (%) and odds ratios (ORs) with 95% confidence intervals (CIs), with α = 0.05. RESULTS: A total of 173 patients were included; 15 patients (8%) died full code and 158 (91%) died after LoC. Seventy-seven patients (48%) underwent incremental LoC. Age (OR, 1.05; 95% CI, 1.02–1.08; p = 0.0010) and female sex (OR, 3.71; 95% CI, 1.01–13.64; p = 0.0487) increased the odds of LoC; number of anatomic injuries (OR, 0.91; 95% CI, 0.85–0.98; p = 0.0146), chest injuries (Abbreviated Injury Scale [AIS] score chest, >3) (OR, 0.02; 95% CI, 0.01–0.26; p = 0.0021), extremity injury (AIS score, >3) (OR, 0.08; 95% CI, 0.01–0.64; p = 0.0170), and hospital complications equal to 1 (OR, 0.21; 95% CI, 0.06–0.78; p = 0.0201) or ≥2 (OR, 0.19; 95% CI, 0.04–0.87; p = 0.0319) decreased the odds of LoC. For those having LoC, final limitations were implemented in <14 days for 83% of patients; markers of injury severity (e.g., Injury Severity Score, Glasgow Coma Scale score, and AIS score) increased the odds of early LoC implementation. CONCLUSION: Most patients died after LoC was implemented in a timely fashion. Significant head injury increased the odds of LoC. The number of injuries, severe chest and extremity injuries, and increasing number of complications decreased the odds of LoC, presumably because patients died before LoCs were initiated. Understanding factors contributing to end-of-life care could help guide discussions regarding LoCs. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III. Abstract :